2016
DOI: 10.4028/www.scientific.net/msf.840.394
|View full text |Cite
|
Sign up to set email alerts
|

Waste Banana Peel and its Potentialization in Agricultural Applications: Morphology Overview

Abstract: The reserach is focused on the resistance of bio-polymer thin film to bio-degradation in compost soil from renewable resources based on waste banana peel and waste egg shell in polymer matrix. The combination of waste banana peel and waste egg shell in producing of bio-mulching film is a new inovation in agricultural industry . Bio-mulching film is a biodegradable plastics films that can help in increasing the moisture content of soil and improving the soil ingredients in order to make the plants grow well. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The powder XRD patterns are depicted in Figure for ZR1 and ZR2 samples having sharp peaks, indicating the noncrystalline nature of the synthesized materials. The powder patterns obtained match the standard powder patterns (JCPDS card 00-003-0569) . The sharp peak at the corresponding 26.60 2θ value for ZR1 and ZR2 in the PXRD pattern corresponds to the (002) planes of carbon materials, whereas ZR2 has a sharp signal at the 23.05 2θ value, which is due to Fe impregnation and matches well with the crystalline iron species akaganeite (β-FeOOH) .…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The powder XRD patterns are depicted in Figure for ZR1 and ZR2 samples having sharp peaks, indicating the noncrystalline nature of the synthesized materials. The powder patterns obtained match the standard powder patterns (JCPDS card 00-003-0569) . The sharp peak at the corresponding 26.60 2θ value for ZR1 and ZR2 in the PXRD pattern corresponds to the (002) planes of carbon materials, whereas ZR2 has a sharp signal at the 23.05 2θ value, which is due to Fe impregnation and matches well with the crystalline iron species akaganeite (β-FeOOH) .…”
Section: Resultssupporting
confidence: 67%
“…The powder patterns obtained match the standard powder patterns (JCPDS card 00-003-0569). 22 The sharp peak at the corresponding 26.60 2θ value for ZR1 and ZR2 in the PXRD pattern corresponds to the (002) planes of carbon materials, 23 whereas ZR2 has a sharp signal at the 23.05 2θ value, which is due to Fe impregnation and matches well with the crystalline iron species akaganeite (β-FeOOH). 24 The results of this study found that impregnated iron existed as both crystalline and amorphous species as broad and sharp peaks observed in the PXRD pattern, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…For instance, RHA is now being studied for its possible use in water treatment,64 brick manufacture,65 light‐emitting diode (LED) applications, etc 66. On the other hand, food wastes are being explored for use in tissue‐engineering applications,67 enhancing soil quality,68 synthesizing environment‐friendly catalysts,37 biodiesel production, etc 69. Many research groups have been exploring methods for the effective utilization of agro‐food wastes for several potential applications .…”
Section: Introductionmentioning
confidence: 99%
“…The exponential increase of world's population and the trend toward the utilization of eco‐friendly and viable agricultural by‐products creates a steady platform for the continuation of innovation on development of products from the banana by‐products and waste, thus, making it a sustainable income generating commodity. Generating wealth from waste such as from the banana by‐products should be regarded as one of the ways to create an eco‐friendly environment for the future generations (Nik Yusuf et al, 2016; Padam, Tin, Chye, & Abdullah, 2014).…”
Section: Introdutionmentioning
confidence: 99%